Surveillance capitalism dalam film the Great Hack: Dampak pada budaya dan politik - Prasetyo, Nur Cahyo Agung; Rahmanto, Andre Noevi; Sudarmo, Sudarmo (Jurnal Praksis dan Dedikasi Sosial, 2025)
Surveillance capitalism in the Great Hack: Impacts on culture and politics The rapid development of digital technology and social media has led to significant transformations in collecting and utilizing personal data, raising concerns about privacy and socio-political dynamics. This study aims to analyse the impact of personal data usage in shaping cultural, social, and political landscapes through a case study of the documentary film The Great Hack. Employing a qualitative approach with content analysis, the study reveals that personal data has become an economic asset exploited for social and political manipulation. The findings indicate that entities like Cambridge Analytica influence individual behaviour and political outcomes through data-driven algorithms, as explained by surveillance capitalism and mediatization theories. The study concludes that personal data exploitation profoundly impacts social structures and political systems, underscoring the need for stringent regulations and public awareness to protect privacy in the digital era. Pesatnya perkembangan teknologi digital dan media sosial telah memunculkan transformasi signifikan dalam pengumpulan dan pemanfaatan data pribadi, menimbulkan kekhawatiran terkait privasi serta dinamika sosial-politik. Penelitian ini bertujuan untuk menganalisis dampak penggunaan data pribadi dalam membentuk lanskap budaya, sosial, dan politik melalui studi kasus film dokumenter the Great Hack. Dengan pendekatan kualitatif menggunakan analisis isi, penelitian ini mengungkap bahwa data pribadi telah bertransformasi menjadi aset ekonomi yang dieksploitasi untuk manipulasi sosial dan politik. Temuan menunjukkan bahwa entitas seperti Cambridge Analytica mampu memengaruhi perilaku individu dan hasil politik melalui algoritma berbasis data, sebagaimana dijelaskan melalui teori surveillance capitalism dan mediatization. Penelitian ini menyimpulkan bahwa eksploitasi data pribadi memiliki dampak besar pada struktur sosial dan sistem politik, sehingga diperlukan regulasi ketat dan peningkatan kesadaran publik untuk melindungi privasi di era digital.